The Mercury Project a feasibility study for Internet robots. - Goldberg, K.
Initiated at CERN in 1992, the World Wide Web provides a standard graphical interface to the Internet, and the number of users worldwide has grown exponentially in the last few years. In the Spring of 1994, we conjectured that it might be possible to offer public access to a teleoperated robot via the WWW. As a feasibility study in 1994, we built a system that allows a robot manipulator to be teleoperated via the Internet. Although the field of teleoperation dates back over 50 years, HTTP provides a low-cost and widely available interface that can make teleoperated resources accessible to a broad range of users. The Mercury Project consisted of an industrial robot arm fitted with a CCD camera and a pneumatic system. We placed a sandbox filled with buried artifacts in the robot workspace. Novice users remotely moved the camera to view desired locations and directed short bursts of compressed air into the sand to view the newly cleared regions. To our knowledge, the Mercury Project was the first Internet robot. It was available almost continuously from August 1994 through March 1995 and was accessed by over 50,000 unique hosts. The article focuses on the interface design, robot hardware, and architecture of the system
Keywords: CCD camera; Internet robots; Mercury Project; World Wide Web; Feasibility study; Graphical interface; Industrial robot arm; Interface design; Minimalist robotics; Pneumatic system; Public access; Robot hardware; Teleoperated resources; Teleoperated robot